الضغط النفسي لدى تلاميذ مرحلة التعليم الثانوي وعلاقته بظاهرة العنف المدرسي دراسة ميدانية بثانوية الجودي بالاغواط - بودبوس بسمة; بقيرة حنان; الشارف سعدية (My University, 2023)
The study aims to identify the relationship between psychological immunity and death anxiety, as the study was then applied to a sample of Covid 19 patients in the interest of Covid with 240 beds, where the study sample reached 30 individuals of both sexes by relying on the tools of the psychological immunity scale and the death anxiety scale and based on the statistical package program For social sciences, we reached the following results: The presence of an average level of psychological immunity among the sample members •There is an average level of death anxiety among the sample members •There are statistically significant differences in psychological immunity due to the gender variable •There are statistically significant differences in the level of death anxiety due to the gender variable •There is a statistically significant relationship between psychological immunity and death anxiety among the sample members Keywords: psychological immunity, death anxiety, covid 19